THE RIGHT TO VOTE FOR PEOPLE WITH MENTAL / MEMORY DISORDERS IN LAW NO. 07 OF 2017 ON ELECTIONS (Study of Fiqh Siyasah Analysis) - Putri Eka Ramadhani Batubara (NOMOI Law Review, 2022)
The subject matter discussed is how the right to vote for people with mental / memory disorders in Law No. 07 of 2017 on General Elections and fiqh Siyasah's analysis of the law. The type of research method used is a method of literature research that is normative juridical, with a statute approach (statute approach) that is to examine all laws related to the subject that aims to see consistency and perness between one regulation with another. From the results of this study it can be concluded that Law No. 07 of 2017 on General Elections has differences regarding voting rights for people who are mentally disturbed / memory of the Constitutional Court Decision No. 135 / PUU / -XIII / 2015. This is because the general election law does not limit the right to vote for people who are disturbed by the soul / memory so that they experience legal vacancies and legal uncertainties that cause multi-interpretation of the law, while the Constitutional Court Decision No. 135 / PUU / -XIII / 2015 clearly and unequivocally ruled that people with mental disorders / memories cannot vote in general elections. and technically it is proven through the certificate of a health expert.Keywords: Consistency, Right, Vote, Siyasah.